Development of Healthy Chili Paste Products from Sacha Inchi (Plukenetia volubills L.) - Kaikaew, Doungtip; Chaleansit, Orathai; Thawerattanon, Nuttanun (Recent Science and Technology, 2023)
The purpose of the research on the development of healthy burnt water products from Sacha Inchi (Plukenetia volubilis L.) is to develop a healthy chili paste recipe from Sacha Inchi derived from the recipe of chili paste with dried shrimp by using Sacha Inchi to replace the amount of dried shrimp and to study the shelf life of healthy chili pastes from developed Sacha Inchi. In the development of the recipe, the chili paste is made by selecting a recipe for chili paste with dried shrimp as an through 4 recipes and 12 food experts to conduct sensory evaluations. It found that the best chili paste formula to be developed included 12% chili peppers, 12% shallots, 12% garlic, 15% sugar, 10% fish sauce, 8% tamarind juice, 6% water, 15% oil and 10% dried shrimp, with an average overall preference rating of a considerable level (8.70). Dried shrimp was replaced with dehydrated Sacha Inchi with microwave oven with a voltage of 220 volts, 50 hz for 5 minutes in volume 10, 20, 30, and 40% of the amount of dried shrimp in the mixture and evaluated by sensory tests, and quality of chili paste was measured by color, free water content, peroxide and nutritional value. The results found that the chili paste formula, which uses 10 % of Sacha Inchi to replace dried shrimp, scored a large average overall preference rating (8.65), brightness (L*), red (a*), yellow value (b*) and free water content (aw) of 26.42, 2.98, 1.46 and 0.80, respectively. Peroxide content of 8.23 mg of oxygen peroxide was equipped with 1 kg of oil and aflatoxin was not found. The total amount of microorganisms, yeast and fungus content was less than 10 colonies per gram. It contains moisture content, protein, fat, carbohydrates, ash, fiber, and energy equal to 25.12 %, 22.04%, 20.70%, 37.60%, 1.38%, 5.11%, and 398 kcal, respectively. Regarding the shelf life accelerated with temperatures (Q10) at 25 and 35 °C, the storage time is 63 and 28 days, respectively. The Q10 value is 2.25, which makes it possible to predict the shelf life of products at 5 oC and 10 oC for 318 days and 212 days.